Super-hydrophilic and in Water Superoleophobic Kaolin Modified Polysulfone (PSF) Microfiltration Membrane for Oily Water Purification: A Research - Khairul Anuar, Nurnajiha Aisyah; Abd Aziz, Mohd Haiqal; Hairom, Nur Hanis Hayati; Razali, Nor Faizah (Progress in Engineering Application and Technology, 2023)
Abstract sentences introduces the research background information and problem statement. It also described about the material, processes and method used for conducting the study. The sentences also explained the objective of the study in order to solve the problem.